Medien der Offenbarung Visionsdarstellungen im Mittelalter - Ganz, David (Reimer Verlag, 2008)
Complementary to revelation in the Word, Christianity depends on visual media that provide insight into the realm of the otherwise invisible. One such medium for the Christian Middle Ages is the vision, which, however, needs to be translated into material images in order to be accessible not only to the eye of a few chosen ones, but also to a larger circle of viewers. In a diachronic perspective, the book takes a look at three different media constellations that shape the history of the representation of visions between the early and late Middle Ages: Vision as written image (early medieval Apocalypse manuscripts, vision books of Hildegard of Bingen and Birgitta of Sweden), Vision as interior space (representations of dreams and the Ascension, English Apocalypse cycles, Adoration diptychs), and Vision as body-sign (the stigmatizations of Francis and Catherine of Siena, representations of the Gregory Mass). The history of medieval representations of visions thus not only provides useful information about the high value of image-based communication within a (supposed) " written religion," it also brings to light a prehistory of those more open concepts of image and media that have replaced the mimesis-based easel painting of modern times since the modern era.